The Role of Money and Fashion in Character Building in Confession of A Shopaholic Movie - Nimas Kharisma Mahanani; Johny Alfian Khusyairi (Hasanuddin University, 2022)
This article discusses the film Confession of A Shopaholic, directed by P.J. Hogan based on Georg Simmel's sociology of money to dismantle the role of money and fashion in the formation of the main character's character. The purpose of this article is to formulate how money problems can change individual character. Georg Simmel's sociology of money points discussed in this article cover two things, namely money as an institution that supports social stratification and the financial system as part of the evolution of society. Simmel's view of fashion is used to support this research. Research data is taken from scenes or dialogues of the main characters in shopping, including when faced with choices. There is a deep connection between money, fashion, social stratification, and the results of the evolution of society which play a role in building the mentality of society itself. Childhood experiences also shape the individual's passion to fulfill his desires as an adult. The results of the study show that the cooperation between money and goods offered by the market is able to drive the emotional side of the individual and the role of the environment to support individuals in finding awareness